Cover Image, Volume 5, Number 3, March 2023. Issue 3 (23rd March 2023) - Yang, Jun; Li, Xing; Qu, Ke; Wang, Yixian; Shen, Kangqi; Jiang, Changhuan; Yu, Bo; Luo, Pan; Li, Zhuangzhi; Chen, Mingyang; Guo, Bingshu; Wang, Mingshan; et al.
Abstract : Front cover image : Lithium metal battery matched with high nickel cathode is a promising energy storage scheme. However, developing an electrolyte that can simultaneously match the robust oxidizing cathode and the reducing lithium metal anode is challenging. In article number CEY2275, Yang et al. developed a new high‐concentration ternary lithium salt ether‐based electrolyte to make commercial high‐mass loading high‐nickel NMC (LiNi0.6Co0.2Mn0.2O2) cathode and thin anode lithium metal battery stable cycling at 4.5V. The optimization mechanism is analyzed from solvent sheath structure, solid electrolyte interface (SEI), and cathode lattice transition. This work provides new insight into high‐voltage lithium metal battery electrolyte.